The Role of the Descobrimento National Park for Regional Sustainability from the Perspective of Stakeholders - Rocha, Sirleide Santana; Neves, Frederico Monteiro; Neves, Joanna Maria da Cunha de Oliveira Santos (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Conservation Units (CUs) are spaces created to maintain the integrity of ecosystems and their biodiversity. The creation of these spaces promotes changes in environmental and cultural dynamics, which can generate conflicts. The aim of this study is to analyze the role of the Descobrimento National Park (DNP) to regional sustainability, considering socio-environmental conflicts as important indicators of the relationship between the CU and the surrounding territory. To this end, the perceptions of the members of the DNP Advisory Council were assessed through semi-structured interviews. The results show that the members’ perceptions are aligned regarding biodiversity protection. However, there are conflicting views on the relationship between the CU and the indigenous communities, which could limit the cooperation of the council members and their relationship with the communities. The signing of the Term of Commitment between the Pataxó Indigenous Community and the management of the CU is highly symbolic and indicates the potential for regional cooperation.